TOPENG ROH ASMAT SEBAGAI IDE PENCIPTAAN KARYA SENI LUKIS - Kangganam, Yohanis Paulus; Suseno, Bayu Aji; Mukkadam, Sarah Sabrina (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
The purpose of designing this artwork is to be a suggestion for the continuity of maintaining the noble traditions and culture of the Asmat tribe, to be a means of knowledge of cultural science between generations, and to be a means of spiritual respect for ancestral spirits. Data collection methods include observation and documentation. Observations observe the activities of the spirit mask party ceremony or ritual using the interview method with informants of the object of research Spirit Mask and the subject of research, informants. Documentation is done by collecting data from several studies such as books, scientific articles, popular articles, magazines, photographs, and videos. The research on the Asmat spirit mask was carried out by the author based on the following stages: first, efforts to find ideas or concepts; second, data collection; third, data analysis is carried out by designing or making representations of the spirit mask folklore and documentation in the form of videos and photos; fourth, data visualization in the form of paintings; fifth, data presentation in the form of an art exhibition, and scientifically accounted for through written works. The tools and materials needed for making paintings include paint, pencils, paint brushes, sand beads, broomsticks. Canvas and bark as media for painting while for installation works are broomsticks and glue guns. The creation of paintings and installation artworks of spirit masks begins with a pencil sketch followed by paint.